Analysis of Indonesian Language Proficiency Among Early Childhood Learners in Pandeyan Village, Maospati Sub-district, Magetan Regency, Using Illustrated Storybooks - Heni Purwulan; Ruminingsih Ruminingsih (Jurnal Ragam Pengabdian, 2026)
Teachers and students use Indonesian as a communication tool to facilitate productive interactions throughout the daily learning process. The author conducted observations of PAUD/TK in Pandeyan Village, Maospati District, Magetan Regency. There is a grammar between students and teachers during classroom learning that is still not good, because it is mixed with local languages or the lack of students' ability to speak well. This is caused by the family background of students who use local languages as their daily language. Kemala Bhayangkari 59 Kindergarten and Sosiawati Kindergarten have implemented a learning model using picture story media to improve their students' language skills, so it is necessary to assess and study the level of success of these efforts. Purpose: The purpose of this study is to measure the level of Indonesian language skills of students in Pandeyan Village Kindergarten, Maospati District, Magetan Regency by implementing a learning model with picture story media. Method: This study uses a qualitative method with data collection techniques through interviews and observations, then presented in the form of words and sentences, then discussed, analyzed and described together with relevant theories and empirical study results. Results: Both schools have implemented illustrated storytelling media in their learning as an effort to improve students' language skills. Based on information and observations, illustrated storytelling media is able to improve children's language skills, but further development is needed with the assistance and collaboration of parents at home, especially for children who are accustomed to using their regional language or mother tongue at school.